Spiky Nickel Electrodes for Electrochemical Oxygen Evolution Catalysis by Femtosecond Laser Structuring - Felix Rieck genannt Best; Jürgen Koch; Gerhard Lilienkamp; Franz Körkemeyer; Hans Jürgen Maier; Jürgen Caro; Karsten Lange (International Journal of Electrochemistry)
Micro- and nanostructured Ni/NiO surfaces were generated by femtosecond laser structuring for oxygen evolution reaction in alkaline water electrolysis cells. For two different angles between the laser beam and the nickel surface, two different types of laser-structured electrodes were prepared, characterized, and compared with a plane tempered nickel electrode. Their electrochemical activities for the oxygen evolution reaction were tested by using cyclic and linear sweep voltammetry. The chemical surface composition was investigated by X-ray photoelectron spectroscopy. Laser structuring increased the overall electrochemical performance by more than one order of magnitude. The overpotential of the laser-structured electrodes for the oxygen evolution reaction was decreased by more than 100 mV due to high defect densities of the structures created by the laser ablation process.